Anthracene-assisted inverse transport growth and superconductivity at 3.3 K in unsupported ultrathin {110} Nb and {0001} NbSe2 nanoplates. Issue 37 (18th September 2017) - Li, Jian-Min; Fang, Jie
Abstract : High-quality ultrathin {0001} NbSe2 and {110} Nb nanoplates via anthracene vapor-assisted hierarchical collapse of constituent NbSe2 . Abstract : An anthracene vapor-assisted inverse transport growth mechanism of unsupported ultrathin two-dimensional (2D) superconducting single-crystal niobium (Nb) and niobium diselenide (NbSe2 ) nanoplates (thickness ∼2.5 nm) using anthracene and NbSe2 powders as precursors is reported. Besides the whisker-like counterparts, the anthracene vapor hierarchical invasion into NbSe2 leads to 2D Nb nanoplates with a {110} surface and 2D few-layered {0001} NbSe2 nanoplates grown in the high-temperature residual region, while sub-millimeter selenium whiskers are found in the low-temperature transporting region. Direct magnetization measurements demonstrated that superconductivity at ∼3.3 K was clearly observed in the unsupported ultrathin Nb and NbSe2 nanoplates. These findings may offer a new way to produce freestanding single-crystal 2D superconductors and elemental 2D metallic nanoplates.